Perspectives of Aboriginal issues among non‐Aboriginal residents of rural Victorian communities. Issue 3 (19th August 2017) - Bourke, Lisa; Malatzky, Christina; Terry, Daniel; Nixon, Raelene; Ferguson, Karyn; Ferguson, Peter
Abstract: Racism, in various forms, remains a dominant feature in Australian society. Aboriginal Australians are commonly targets of racial discrimination. However, understanding racism is difficult given that racial attitudes vary towards particular groups of people, across place and time and are difficult to measure. This paper presents responses of residents across four rural shires in Victoria to questions about attitudes towards Aboriginal people/issues. Responses indicated that attitudes towards Aboriginal people were diverse and that individuals varied in their attitudes on specific items. There were subtle differences between the four sites and association between demographic characteristics and some items in particular sites. This suggests that respondents are inconsistent in their attitudes relating to Aboriginal people/issues and that there are place‐based influences on these attitudes. We conclude that the many varied understandings of racism and Aboriginal Australians allow the discourses of exclusion, disempowerment and othering to be maintained.